Analisis Pengaruh Proporsi Tenaga Kerja dan Eksternalitas Aglomerasi Terhadap PDRB Industri Sektor Manufaktur di Indonesia - Widya Utari; Fitrawaty Fitrawaty; Dede Ruslan (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the effect of labor proportion and industrial agglomeration externalities on the Gross Regional Domestic Product (GRDP) of the manufacturing sector in Indonesia. This research employs a quantitative approach using panel data covering 34 provinces over the period 2019–2023. The independent variables include labor proportion and industrial externalities represented by specialization index (MARshall–Arrow–Romer/MAR), competition (Porter), and diversity (Jacobs). The analysis method uses panel data regression with model selection through Chow, Hausman, and Lagrange Multiplier tests, where the Random Effect Model (REM) is selected as the best estimation model. The results show that labor proportion and MAR externalities have a positive and significant effect on manufacturing GRDP, highlighting the important role of labor and industrial specialization in driving regional output growth. In contrast, Porter and Jacobs externalities do not have a significant effect, indicating that industrial competition and diversity have not yet contributed substantially to manufacturing sector performance during the study period. Simultaneously, all independent variables significantly affect GRDP, although the model’s explanatory power remains relatively limited. These findings suggest that the growth of Indonesia’s manufacturing sector is more influenced by labor and industrial concentration rather than competition and diversification dynamics, and that other factors outside the model also play an important role in determining manufacturing sector performance.